The place of nurses in our society today - B. M. Gourley (AOSIS, 1995)
You can ask just about anyone you know about what they consider to be the most important jobs in our society and you can be sure that they will include nurses and teachers in their list. Such jobs are so important and require such dedication that it is common to refer to them as 'vocations' rather than jobs. The dictionary definition of 'vocation' uses words like 'calling' indicating that not all people are equipped for such tasks. And so it is with particular pleasure that I add my personal good wishes to the very special people who are dedicating themselves here this evening. As a society I believe we are indebted to you and your colleagues who choose to spend your lives in the service of others and 1 am sure you will find satisfaction and fulfilment in the process.